2022
DOI: 10.3390/antiox11122342
|View full text |Cite
|
Sign up to set email alerts
|

Thiocyanate Reduces Motor Impairment in the hMPO-A53T PD Mouse Model While Reducing MPO-Oxidation of Alpha Synuclein in Enlarged LYVE1/AQP4 Positive Periventricular Glymphatic Vessels

Abstract: Parkinson’s disease (PD) is due to the oxidation of alpha synuclein (αSyn) contributing to motor impairment. We developed a transgenic mouse model of PD that overexpresses the mutated human αSyn gene (A53T) crossed to a mouse expressing the human MPO gene. This model exhibits increased oxidation and chlorination of αSyn leading to greater motor impairment. In the current study, the hMPO-A53T mice were treated with thiocyanate (SCN−) which is a favored substrate of MPO as compared to chlorine. We show that hMPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…Myeloperoxidase (MPO) increases nitration and aggregation of 𝛼-Syn, and the oxidants it generates damage the glymphatic drainage system. [16,69] Reynolds et al showed that thiocyanate, as a substrate of MPO, could inhibit MPO chlorination/oxidation to decrease the impairment of the glymphatic pathway and suppress the development of PD. [16] Besides, blockage of the meningeal lymphatics may also affect the glymphatic system both in animals and humans.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Myeloperoxidase (MPO) increases nitration and aggregation of 𝛼-Syn, and the oxidants it generates damage the glymphatic drainage system. [16,69] Reynolds et al showed that thiocyanate, as a substrate of MPO, could inhibit MPO chlorination/oxidation to decrease the impairment of the glymphatic pathway and suppress the development of PD. [16] Besides, blockage of the meningeal lymphatics may also affect the glymphatic system both in animals and humans.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…[16,69] Reynolds et al showed that thiocyanate, as a substrate of MPO, could inhibit MPO chlorination/oxidation to decrease the impairment of the glymphatic pathway and suppress the development of PD. [16] Besides, blockage of the meningeal lymphatics may also affect the glymphatic system both in animals and humans. [50,67] Table 1.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
See 2 more Smart Citations